Tanggung Jawab Direksi Perseroan Terbatas Atas Perbuatan Melawan Hukum Di Indonesia - Muhammad Rizqy Putra (Universitas Islam Indonesia, 2021)
This research is motivated by legal problems that occur in Dasep Ahmadi and Hotasi Nababan, both of whom have committed acts against the law in their duties as directors who run the company. The problems to be answered in this research are how the responsibility of the board of directors of a limited liability company for unlawful acts committed by the board of directors in Indonesia and how is the legal remedies for the loss of the company due to unlawful acts committed by the board of directors in managing a limited liability company. This research using normative juridical method. The results of this study conclude that first, unlawful acts become a problem for the board of directors in managing the company, as a result the company suffers losses, the negligence of the directors in managing the company legally requires the directors to take full personal responsibility as stipulated in Article 97 paragraph (3) of the Company Law. Second, Dasep Ahmadi and Hotasi Nababan have carried out their personal responsibility in accordance with these provisions and for the fulfillment of compensation for the company, they can file a claim for compensation based on Article 61 paragraph (1) and Article 97 paragraph (6) of the Limited Liability Company Law and/or file a claim for compensation. losses based on unlawful acts as regulated in Article 1365 of the Civil Code.Key Words: Limited liability company; responsibilities of directors; unlawful actsAbstrakPenelitian ini dilatarbelakangi permasalahan hukum yang terjadi pada Dasep Ahmadi dan Hotasi Nababan, keduanya sama-sama telah melakukan perbuatan melawan hukum dalam tugasnya sebagai direksi yang mengurus perseroan. Permasalahan yang ingin dijawab dalam penelitian ini adalah bagaimana tanggung jawab direksi perseroan terbatas atas perbuatan melawan hukum yang dilakukan oleh direksi di Indonesia dan bagaimana upaya hukum atas kerugian perseroan akibat perbuatan melawan hukum yang dilakukan oleh direksi dalam mengurus perseroan terbatas. Penelitian menggunakan metode yuridis normatif. Hasil penelitian menyimpulkan, pertaman, bahwa perbuatan melawan hukum menjadi permasalahan bagi direksi dalam melakukan pengurusan perseroan, akibatnya perseroan mengalami kerugian, kelalaian direksi dalam pengurusan perseroan mewajibkan secara hukum direksi mengambil tanggung jawab penuh secara pribadi sebagaimana ketentuan Pasal 97 ayat (3) UU PT. Kedua, Dasep Ahmadi dan Hotasi Nababan telah melakukan tanggung jawab secara pribadi sesuai dengan ketentuan tersebut dan untuk pemenuhan ganti kerugian terhadap perseroan, bisa melakukan gugatan ganti kerugian berdasarkan Pasal 61 ayat (1) dan Pasal 97 ayat (6) UU PT dan/ atau mengajukan gugatan ganti kerugian berdasarkan perbuatan melawan hukum sebagaimana yang diatur Pasal 1365 KUHPerdata.Kata Kunci: Perseroan terbatas; perbuatan melawan hokum; tanggung jawab direksi